Keratinocyte cancer excisions in Australia: Who performs them and associated costs. (22nd April 2019) - Thompson, Bridie S; Pandeya, Nirmala; Olsen, Catherine M; Dusingize, Jean Claude; Green, Adele C; Neale, Rachel E; Whiteman, David C
Abstract: Background/Objective: To describe the clinical settings in which keratinocyte cancers are excised in Queensland and describe the types of practitioners who excise them; to examine costs; and to identify predictors of hospital admission. Methods: We used linked data for participants from the QSkin study ( n = 43 794), including Medicare claims and Queensland hospital admissions relating to treatment episodes for incident keratinocyte cancers from July 2011 to June 2015. We used multinomial logistic regression to measure associations between demographic and clinical characteristics and treatment setting. The median costs of Medicare claims (AU) were calculated. Results: During 4 years of follow‐up, there were 18 479 skin cancer excision episodes among 8613 people. Most excisions took place in private clinical rooms (89.7%), the remainder in hospitals (7.9% private; 2.4% public). Compared with other anatomical sites, skin cancers on the nose, eyelid, ear, lip, finger or genitalia were more likely to be treated in hospitals than in private clinical rooms (public hospital OR 5.7; 95%CI 4.5–7.2; private hospital OR 8.3; 95%CI 7.3–9.4). Primary care practitioners excised 83% of keratinocyte cancers, followed by plastic surgeons (9%) and dermatologists (6%). The median Medicare benefit paid was 253 in private clinical rooms and 334 in private hospitals. Out‐of‐pocket payments by patients treated in private hospitals were fourfold higher than those in private clinical rooms (351 vs 80). Conclusions: Most keratinocyte cancers are excised in primary care, although more than 10% of excisions occur in hospital settings.